Advanced utilization of 3D digital image correlation for thermal and impact reliabilities of electronics components. Issue 1 (29th January 2021) - Kwak, Jae B.; Chung, Soonwan
Abstract : Purpose: This paper aims to present an adaptation of digital image correlation (DIC) to the electronics industry for reliability assessment of electronic packages. Two case studies are presented: one for warpage measurement of a micro-electro-mechanical system (MEMS) package under different temperature conditions and the other for the measurement of transient displacements on the surface of a printed circuit board (PCB) assembly under free-fall drop conditions, which is for explaining the typical camera setup requirement and comparing among different boundary conditions by fastening methods of PCB. Design/methodology/approach: DIC warpage measurements on a small device, such as a MEMS package, require a special speckle pattern. A new method for the creation of speckle patterns was developed using carbon coating and aluminum evaporative deposition. To measure the transient response on the surface of a PCB during a free-fall impact event, three-dimensional (3D) DIC was integrated with synchronized stereo-high speed cameras. This approach enables the measurement of full-field displacement on the PCB surface during a free-fall impact event, contrary to the localized information that is obtained by the conventional strain gage and accelerometer method. Findings: The authors suggest the proposed patterning method to the small-sized microelectronics packages for DIC measurements. More generally, the idea is to have a thin layer of the dark or bright color of the background and then apply the white or black colored pattern, respectively, so that the surface has high contrast. Also, to achieve a proper size of speckles, this paper does not want to expose the measuring objects to high temperatures or pressures during the sample preparation stage. Of course, it seems a complicated process to use aluminum evaporator, carbon coater and electroformed mesh. However, the authors intend to share one of the solutions to achieve a proper pattern on such small-sized electronic packages. Originality/value: 3D DIC technique can be successfully implemented for the measurement of micro-scale deformations in small packages (such as MEMS) and for the analysis of dynamic deformation of complex PCB.